The health interests and needs of freshmen college students of the University of the Philippines - Enriquez, Magdalena A. 1931-
Health needs and health interests of freshman college students of the University of the Philippines are investigated in this study to serve as a basis for providing the most meaningful health experiences for boys and girls.